Active search about latex in injectable drugs for patient's safety in medical therapy - Roberta G. PEIXE; Maria C. SODRÉ; Beatriz B. OLIVEIRA; Luana P. GONÇALVES; Ian G. HALM; José C. CRUZ; Ana P. ANTUNES; Rodrigo T. AMANCIO (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2021)
Objectives: To classify injectable drugs used in a general hospital inventory according to latex presence or absence in vials with rubber stoppers, antibiotics, and electrolytes bags. Methods: The information about latex content has been collected from medicine industries, after identification of authorized manufacturers in Brazil, through the National Health Surveillance Agency (ANVISA) medicine search database. Medicines have been grouped per pharmaceutical manufacturers, and data were collected through telephone or e-mail. Only written information from pharmaceutical companies were considered. Results: Among 161 medicines used in the hospital packaged in vials with rubber stoppers, antibiotics, and electrolytes bags, 123 (76.4%) medicine-related responses were received, covering 540 (82.2%) different presentations. For this, from 87 contacts, 70 (80.5%) companies responded and 65 (74.7%) provided information related to the presence or absence of the allergen. Among the medicine list, 8 (6.5%) were identified as containing latex (in 12 different presentations - 2.2%) and 101 medications (82.1%) in 507 presentations (93.9%) do not contain latex. The manufacturers responded that the medicine was latex-free, but could not confirm for raw materials (6 medicines - 4.9% - in 6 different presentations - 1.1%) and that they were unable to ensure there was no contact with latex during manipulation (4 medicines - 3.3% - in 8 different presentations - 1.5%). For 4 medicines (3.3%) in 7 different presentations (1.3%), the companies were inconclusive, as they could not confirm whether they were latex-free or not. Conclusion: Although latex is a known allergen, information about the presence of latex components in pharmaceutical packaging and package inserts needs improvement, since the active search identified 161 medicines packaged in vials with rubber stoppers, antibiotics, and electrolytes bags that failed to depict this information. The results of this survey endorse the Importance of displaying this information on medicines label or packaging in order to ensure healthcare professionals easy access and prompt consultation.